Risankizumab, an IL-23 inhibitor, for ankylosing spondylitis: results of a randomised, double-blind, placebo-controlled, proof-of-concept, dose-finding phase 2 study. Issue 9 (26th June 2018) - Baeten, Dominique; Østergaard, Mikkel; Wei, James Cheng-Chung; Sieper, Joachim; Järvinen, Pentti; Tam, Lai-Shan; Salvarani, Carlo; Kim, Tae-Hwan; Solinger, Alan; Datsenko, Yakov; Pamulapati, Chandrasena; Visvanathan, Sudha; et al.
Abstract : Objectives: To evaluate the efficacy and safety of risankizumab, a humanised monoclonal antibody targeting the p19 subunit of interleukin-23 (IL-23), in patients with active ankylosing spondylitis (AS). Methods: A total of 159 patients with biological-naïve AS, with active disease (Bath Ankylosing Spondylitis Disease Activity Index score of ≥4), were randomised (1:1:1:1) to risankizumab (18 mg single dose, 90 mg or 180 mg at day 1 and weeks 8, 16 and 24) or placebo over a 24-week blinded period. The primary outcome was a 40% improvement in Assessment in Spondylo Arthritis International Society (ASAS40) at week 12. Safety was assessed in patients who received at least one dose of study drug. Results: At week 12, ASAS40 response rates were 25.5%, 20.5% and 15.0% in the 18 mg, 90 mg and 180 mg risankizumab groups, respectively, compared with 17.5% in the placebo group. The estimated difference in proportion between the 180 mg risankizumab and placebo groups (primary endpoint) was –2.5% (95% CI –21.8 to 17.0; p=0.42). Rates of adverse events were similar in all treatment groups. Conclusions: Treatment with risankizumab did not meet the study primary endpoint and showed no evidence of clinically meaningful improvements compared with placebo in patients with active AS, suggesting that IL-23 may not be a relevant driver of disease pathogenesis and symptoms in AS. Trial registration number: NCT02047110 ; Pre-results.